MAKNA TRADISI “NGAPATI” - Nurul Huda (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2019)
Indonesia is famous for a country full of diverse customs and cultures from various regions. One of the famous customs and cultures in Javanese society is the Ngapati Tradition. A tradition that develops in society is sometimes motivated by a number of factors, whether influenced by the environment, culture and conditions of the community Likewise with the attitude of tradition that exists in the community, sometimes in certain societies the tradition is rejected outright, but in other communities it can be well received. This article will try to explore the meaning of the Ngapati tradition in Deresan Village, Ringinharjo, Bantul, Yogyakarta through the study of living Hadith approaches. The context of the community of Deresan Village is a friendly and open society with a variety of traditions, including the Ngapati tradition, that is practiced in the village is the tradition carried out in descending manner with the intention of praying for the fetus when the fetus is four months old in the womb. For the Deresan community, the tradition was also carried out because it was based on the traditions of the hadith. The Ngapati tradition has become a legacy of generations in human history. The practice of the Ngapati tradition is the result of social construction based on the interpretation of the knowledge of the people who then experience the transmission process.